PRAF2 as a novel biomarker for breast cancer with machine learning and experimentation validation - Zheng Wang; Zilin Bi; Hongguang Bo; Junyi Xu; Rui Sha; Zhaocai Yin; Changsheng Yu; Yufa Xu; Xiaomeng Shi; Wenbo Song; Bin Chen; Yabing Wang; et al. (BMC Cancer)
Abstract Background Breast cancer (BC) is the most prevalent malignancy in women. Potential therapeutic targets for BC are of great significance. In our previous study, we found that prenylated rab acceptor 1 domain family member 2 (PRAF2) is an oncogene in BC. However, the exact mechanism of PRAF2 in BC cancer promotion is still not fully understood. Methods Pan-cancer analysis of PRAF2 was performed in the TIMER, Kaplan‒Meier, UALCAN and GEPIA databases.The prognostic value of PRAF2 in BC was investigated in the GEPIA database. The influence of PRAF2 on immune infiltration in BC was analyzed in the TISIDE and TIMER databases. Finally, we validated the expression of PRAF2 in our institutional samples. After downregulating PRAF2 in two BC cell lines, we tested cell proliferation by CCK-8 and Wound healing assays. Results PRAF2 was highly expressed in various cancers, including BC, and in most BC cell lines. Higher expression of PRAF2 indicated poorer overall survival (OS) but not disease-free survival (DFS). Higher expression of PRAF2 is an independent prognostic factor in BC.PRAF2 is more highly expressed in BC than in the corresponding normal tissues. Downregulation of PRAF2 in BC can significantly inhibit viability and migration. Conclusions PRAF2 is highly expressed in various cancers, including BC. The expression of PRAF2 is related to Liquid–Liquid Phase Separation in BC. Finally, PRAF2 is upregulated in BC based on our institutional data. Downregulation of PRAF2 significantly inhibits cellular viability、migration in BC. PRAF2 may be a potential biomarker and therapeutic target for BC.